Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Denote By $V$ the real vector spaces of all real polynomials in one variable, and let $P : V \rightarrow \mathbb{R}$ be a linear map. Suppose that $\forall$ $f,g \in V$ with $P(fg) = 0$ we have $P(f) = 0$ or $P(g) = 0$. Prove that there exists real numbers $x_0, c$ such that $P(f) = cf(x_0)$ for all $f$.

share|improve this question

2 Answers 2

up vote 8 down vote accepted

It's enough to show is true for $f(x)=x^k , \ \ k\in \mathbb{N}\cup\{0\}.$

Define $c=P(1)$ and assume $c\neq 0$. Then define $P\left(\dfrac{x}{c}\right)=x_0$ and assume that $\ x_0 \neq 0$. Now show, using induction, that $P(x^k)=cx_0^k, \ \forall k \in \mathbb{N}$.

For example for $k=2$:
$P(x^2)=r \in \mathbb{R} \Rightarrow P(r\frac{x}{cx_0}-x^2)=0 \Rightarrow P(x)=0 \text{ or } P(\frac{r}{cx_0}-x)=0$. Since $P(x) \neq 0$ we get $P(\frac{r}{cx_0})=P(x) \Rightarrow \frac{r}{cx_0}P(1)=c x_0 \Rightarrow r=c x_0^2$. Thus $P(x^2)=r=cx_0^2$.

Next we consider the cases $c=0$ or $x_0=0.$

  • $c\neq0$ and $x_0=0$:
    We have $P(x+1)=c$. For $k\geq 2, \ \text{if} \ \ P\left((x+1)^k\right)=r \Rightarrow P\left((x+1)^k-\frac{r}{c}(x+1)\right)=0.$
    Since $P\left((x+1)\right)\neq0 \Rightarrow P\left((x+1)^{k-1}-\frac{r}{c}\right)=0 \Rightarrow P\left((x+1)^{k-1}\right)=\frac{r}{c}P(1)=r$.
    Now use induction to show that $P\left((x+1)^k\right)=c \ \forall k \in \mathbb{N}$.
    Then use induction to show that $P\left(x^k\right)=0 \ \forall k \in \mathbb{N}$ (use that $x^k=(x+1)^k-kx^{k-1}-\ldots-kx-1$).
  • $c=0$:
    If $P(x^k)=r\neq 0$ for some $k \in \mathbb{N}$ then $P(x^{2k})=s\neq0$. Since $P\left(x^{2k}-\frac{s}{r}x^k\right)=0 \Rightarrow P\left(x^k\right)=0 \ \text{or} \ P\left(x^k-\frac{s}{r}\right)=0$. In either case we get $P\left(x^k\right)=0$↯.
    Therefore $P\left(x^k\right)=0 \ \forall k \in \mathbb{N}$.
share|improve this answer
    
How can you solve the cases c = 0 or x_0 = 0? –  Learner Nov 24 '12 at 7:14
    
@LJym89 I have updated my answer. –  P.. Nov 24 '12 at 11:26

I read this question just today. After I wrote down a proof, I read Pambos' and found that the two proofs are very similar. So I think I'd better not repeat Pambos' argument here, but only write down the part of my proof that differs the most from Pambos'.

Specifically, consider the second case in Pambos' proof, where $P(1)\not=0$ and $P(x)=0$. By linearity of $P$, we may assume that $P(1)=1$. Let $a_k=P(x^k)$ (hence $a_1=0$). Then for $k>1$, $$P\left((x-a_k)(x^{k-1}+1)\right)=P(x^k)-a_kP(x^{k-1})+P(x)-a_k=-a_ka_{k-1}.$$ Hence by mathematical induction, we can show that $a_k=0$ for all $k>1$. Thus $P(f)=f(0)$.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.